2008
DOI: 10.1164/rccm.200709-1365oc
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Findings in Acute Exacerbation of Idiopathic Pulmonary Fibrosis

Abstract: HRCT extent and patterns are predictive of survival in acute exacerbation of IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
183
2
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(201 citation statements)
references
References 19 publications
3
183
2
9
Order By: Relevance
“…Clinical features are similar in patients with other causes of acute respiratory worsening [24]. HRCT shows a background of fibrotic interstitial lung disease, with superimposed bilateral ground glass changes, with or without consolidation [58]. Transbronchial and surgical lung biopsies are generally avoided since they infrequently alter management and have a high risk of complications.…”
Section: Clinical Features and Diagnostic Evaluationmentioning
confidence: 93%
“…Clinical features are similar in patients with other causes of acute respiratory worsening [24]. HRCT shows a background of fibrotic interstitial lung disease, with superimposed bilateral ground glass changes, with or without consolidation [58]. Transbronchial and surgical lung biopsies are generally avoided since they infrequently alter management and have a high risk of complications.…”
Section: Clinical Features and Diagnostic Evaluationmentioning
confidence: 93%
“…17). In the study of Akira and colleagues, 42 there were significant differences in survival based on this distribution, as follows: diffuse (0% at 100 days), multifocal (50% at 500 days), and peripheral (75% at 500 days). Fig.…”
Section: Acute Exacerbation Of Interstitial Lung Diseasementioning
confidence: 93%
“…First, phase III trial of pirfenidone showed there was a relative reduction of 47.9% in the proportion of patients who had an absolute decline of 10 percentage points or more in the percentage of the predicted FVC or who died over 52 weeks (P<0.001) (65). In addition, pirfenidone had significant effect on reduction for death from any cause (P=0.01) and from IPF (P=0.006).…”
Section: Clinical Trialsmentioning
confidence: 99%